Preliminary application of enhanced recovery after surgery in modified electroconvulsive therapy - Zang Xiangyang, Li Xiaoyue, Zhou Shaoli (Xin yixue, 2022)
Modified electroconvulsive therapy （MECT） is an improved treatment for mental disorders by delivering a proper dose of intravenous anesthetics and muscle relaxants based on traditional electroconvulsive therapy. An increasing number of patients receive MECT at a younger age. Frequent MECT may cause intense psychological stress to the patients. Enhanced recovery after surgery （ERAS） can accelerate postoperative recovery by optimizing perioperative management interventions, mitigating stress response and lowering the risk of postoperative complications. ERAS concept emphasizes multidisciplinary collaboration. In recent years,this concept has been promoted and applied in a variety of surgical procedures. However, the application of ERAS in MECT has been rarely studied. In this article, the management measures and operation procedures of ERAS in MECT were summarized, aiming to provide reference for the standardized implementation of ERAS in MECT.